A phenomenological approach for modelling force enhancement and depression in skeletal muscle tissue. Issue 1 (13th February 2019) - Seydewitz, Robert; Siebert, Tobias; Böl, Markus
Abstract: Skeletal muscles are responsible for numerous amount of different motions in mammals such as running, jumping, and climbing. In order to fully describe the complexity of motions it is important to understand muscle contraction. Experimental investigations revealed a dependency of active forces on the contraction history of muscles, but the theory behind is not well understood. In that sense we suggest a phenomenological model to simulate history effects such as force enhancement and depression.